Clinoconidium inouyei comb. nov. (Cryptobasidiaceae), producing galls on shoot buds of Machilus japonica in Japan - Kakishima, Makoto; Shibata, Saho; Hirooka, Yuuri (Phytotaxa, 2020)
A new combination, Clinoconidium inouyei, is proposed to accommodate Uredo inouyei (syn. Ustilago inouyei, Melanopsichium inouyei, Ustilago machili) from Japan, producing galls on shoot buds of Machilus japonica (Lauraceae). This taxonomic treatment is based on observations of gastroid sporulation in peripheral lacunae of the host galls and basidiospore morphology. This is also supported by phylogenetic analyses with LSU and ITS regions of rDNA. This species is morphologically and phylogenetically similar to C. onumae producing galls on shoot buds of Cinnamomum tenuifolium reported from Japan, but has larger basidiospores.